1974
DOI: 10.1063/1.1663362
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption of mixed silicon isotope pairs in gallium arsenide

Abstract: Absorption saturation in germanium, silicon, and gallium arsenide at 10.6 μm Appl.The infrared absorption of GaAs doped with 2sSi, 30Si, or 2sSi + 3Dgi and compensated by 6Li diffusion or electron irradiation is reported. Isotopic shifts close to those predicted from local-mode theory are observed for all the silicon defect bands in 30Si-doped GaAs from frequencies previously reported for 2sSi_doped material. a new band is observed at 456 cm-I for the sample containing both 2sSi and 30Si, and is attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Manuscript submitted Oct. 29, 1979; revised manuscript received Feb. 13, 1980. This was Paper 578 presented at the Los Angeles, California, Meeting of the Society, Oct. [14][15][16][17][18][19] 1979.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuscript submitted Oct. 29, 1979; revised manuscript received Feb. 13, 1980. This was Paper 578 presented at the Los Angeles, California, Meeting of the Society, Oct. [14][15][16][17][18][19] 1979.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…There has been a considerable volume of literature (2,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) dealing with the detailed behavior of Li in pure and doped GaAs, and as a result of these studies a number of specific defect species involving Li either with native defects or paired with other impurities have been identified. While lithium behaves as an interstitial donor in the elemental semiconductors Si and Ge, it is self-compensating in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Table II at 366.63 cm "1 was a third of the four expected Si pair bands but a number of independent pieces of evidence indicated that this assignment was incorrect. There are several reasons for attributing the two bands mentioned above to a 28Si dimer defect, presumably 28 St Ga-Z SAs' but a convincing observation (8 ) Table II it is apparent for both the peak frequencies and linewidths that the modes are not influenced by the compensation method and therefore they are a property of the GaAs:Si system. From the discussion above it is apparent that there should be a nn GaGa isotope effect on the pair bands because the coupled Si modes involve the vibrational motion of 28Si which has four nn of which three are GaGa and one is SiGa' The nn isotope effect is also suggested by the large FWHM values given in Table II.…”
Section: Ga (Td)mentioning
confidence: 91%
“…In heavily Si‐doped III–V compounds, many ideas have been proposed to comprehend the charge carrier compensation . The electrical deactivation of Si donors ( SiIII+true) was credited exclusively to the Si acceptors ( SiV) via auto‐compensation with the formation of NN Si III –Si V pairs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consequently, several defects are deliberated for electrical deactivation including Si clusters and Si III –V III NNN centers, where V is a vacancy at III‐lattice site. Later type complexes are given special attention as centers of similar configurations (Ge Ga –V Ga , Te As –V As , and S As –V As ) are proven valuable for empathizing electrical decativation in Ge‐, Te‐, and S‐doped n‐type GaAs …”
Section: Theoretical Backgroundmentioning
confidence: 99%